In-situ synthesis of high strength and toughness TiN/Ti6Al4V sandwich composites by laser powder bed fusion under a nitrogen-containing atmosphere. (15th March 2023) - Xiao, Yunmian; Yang, Yongqiang; Wang, Di; Liu, Linqing; Liu, Zibin; Wu, Shibiao; Zhou, Hanxiang; Liu, Zixin; Song, Changhui
Abstract: Laser powder bed fusion (LPBF) additive manufacturing provides the freedom to manufacture the novel bionic structures and materials with excellent mechanical properties ( e.g., combining high strength and toughness). In this work, inspired by the laminar structure of natural shells, the TiN/Ti6Al4V sandwich structural materials were fabricated in the atmosphere with different ratios of nitrogen and argon. The elemental diffusion, in-situ synthesis between N and Ti atoms, microstructure evolution, and mechanical properties of LPBF-processed TiN/Ti6Al4V sandwich composites were investigated. TiN induced by the in-situ synthesis between N and Ti atoms was observed, which exhibited an excellent metallurgical bond with the Ti6Al4V matrix. The microhardness of the TiN/Ti6Al4V layer varied from 409.62 HV0.2 and 442.55 HV0.2 with different nitrogen concentrations. The tensile strength and ductility of LPBF-processed TiN/Ti6Al4V sandwich composite parts were enhanced by the combination of bio-inspired lamellar structure and internal ceramic particle reinforcement. Interlayer hard-soft phase combination in the composite parts could be contributed to the excellent mechanical properties with an ultimate strength of 1303.12 MPa and a plastic strain of 8.9%. This study demonstrates that a flexible combination of the LPBF process and reactive atmosphere can in-situ additive manufacture the novel periodic lamellar ceramic/metal heterogeneous materials with excellent mechanical performance ( e.g., rigid, wear-resistant, corrosion-resistant and toughness). Graphical abstract: Image 1 Highlights: Nitrogen solution and grain refined strengthening to enhanced mechanical properties of LPBF Ti6Al4V alloy. TiN/Ti6Al4V sandwich structure composites were in-situ prepared by LPBF under different nitrogen concentrations. Ti-MSSCs exhibit significantly high strength of ∼1330 MPa and ductility of ∼9%. Interface pinning effect of in-situ synthesized TiN ceramic particles occurred in Ti-MSSCs.